1980
DOI: 10.1111/j.1095-8649.1980.tb02741.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial layers in fish skin

Abstract: Layers of cells limiting the deep face of the dermis and lining the scale pockets can be described as endothelial, using the term in the broad sense. A dermal endothelium has been found in lampreys and in teleosts of diverse form and habits; it consists of a single layer of modified fibrocytes joined by desmosomal and other junctions and having hemidesmosomes and numerous caveolae intracellulares. A fibrous zone interpreted as elastic tissue intervenes between the dermal endothelium and the collagen of the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Epidermal cells from the skin surrounding this wounded surface will cover the wound, a process called re‐epithelialization. Given our experimental conditions, these epidermal cells have to spread on a heterogeneous surface composed of two types of substrates: basement membrane components lining the scale pocket surface (Whitear et al, 1980; Sire, 1989) and collagen fibrils of the cut dermal strips (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Epidermal cells from the skin surrounding this wounded surface will cover the wound, a process called re‐epithelialization. Given our experimental conditions, these epidermal cells have to spread on a heterogeneous surface composed of two types of substrates: basement membrane components lining the scale pocket surface (Whitear et al, 1980; Sire, 1989) and collagen fibrils of the cut dermal strips (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…However, Markl and Franke (1988) have since shown that fish vascular endothelial cells are exceptional in expressing cytokeratins. There is evidence that desmosomes can anchor vimentin-containing IFS (Kartenbeck et al, 1983(Kartenbeck et al, , 1984 but they are normally cytokeratin-associated structures, and it is known that fish are unusual in that various mesothelial tissues, including vascular endothelium, have desmosomes (Whitear et al, 1980). It is of major interest, of course, whether patterns in the tissue distribution of cytoskeletal proteins and junctions reflect underlying developmental or evolutionary restrictions, or represent case-by-case tissue-mechanical requirements.…”
Section: Reinforcing the Optic Nervementioning
confidence: 99%
“…At the deep surface of the stratum compactum, the layer of dermal endothelial cells is flat and delimits the deep dermal region, in which pigment cells are visible, from the muscle cells. This region, considered as the initium of the hypodermis, has been described by Whitear et al (1980) in numerous teleost species. The last change concerns also the dermis, in which the plywood-like stratum compactum is now composed of collagen fibrils of a larger diameter than in the previous stages, about 50 nm.…”
Section: E D Fmentioning
confidence: 99%
“…The deep surface of the hypodermis is interrupted at the level of each myoseptum. A basement membrane separates the epidermis from the dermis and, facing the outer fibrocyte-like layer of the hypodermis, the deep surface of the dermis is lined by a dense zone, resembling a basement membrane (Whitear et al, 1980).…”
Section: Structure and Organisationmentioning
confidence: 99%